Continuous Cardiac Monitoring around Atrial Fibrillation Ablation: Insights on Clinical Classifications and End Points. Issue 8 (19th June 2016) - DEKKER, LUKAS RC; POKUSHALOV, EVGENY; SANDERS, PRASHANTHAN; LINDBORG, KATHERINE A.; MAUS, BÄRBEL; PÜRERFELLNER, HELMUT
Abstract : Background: Atrial fibrillation (AF) is an arrhythmia that can be difficult to identify and classify with short‐term monitoring. However, current standard of practice requires only short‐term monitoring to determine AF classifications and identify symptom‐arrhythmia correlations prior to AF ablation procedures. Insertable cardiac monitors (ICMs) offer continuous arrhythmia monitoring, which could lead to a more accurate measurement of AF burden than standard of practice. Methods: This analysis focused on 121 patients enrolled in the LINQ Usability Study indicated for an AF ablation. Patients were followed for up to 1 year after ICM insertion. Clinical AF classifications were made by physicians prior to ICM implantation based on available clinical information. Device‐detected AF burden and maximum daily burden were collected from device interrogations and remote transmissions. Device AF classifications were determined by categorizing the AF burden based on guidelines. Results: Agreement between clinical and device AF classifications preablation was poor (48.3%, N = 58). The strongest agreement was in the paroxysmal AF group but still was only 61.8%. Furthermore, device‐detected preablation AF burden led to the decision to defer AF ablation procedures in 16 (13.2%) patients. The median AF burden in patients with ≥6 months follow‐up postablation (n = 71) was reduced from 7.8% (interquartile range [IQR]: 0–32.1%) to 0% (IQR: 0–0.7%). Conclusions: ICM monitoring to determine AF burden pre‐ and post‐AF ablation may have clinical utility for management of ablation candidates through more accurate AF classification and guiding treatment decisions.